Quantum Non-Demolition Detection of Polar Molecule Complexes: Dimers, Trimers, Tetramers - Mekhov, I (2011)
The optical nondestructive method for in situ detection of the bound states of ultracold polar molecules is developed. It promises a minimally destructive measurement scheme up to a physically exciting quantum non-demolition (QND) level. The detection of molecular complexes beyond simple pairs of quantum particles (dimers, known, e.g., from the BEC-BCS theory) is suggested, including three-body (trimers) and four-body (tertramers) complexes trapped by one-dimensional tubes. The intensity of scattered light is sensitive to the molecule number fluctuations beyond the mean-density approximation. Such fluctuations are very different for various complexes, which leads to radically different light scattering. This type of research extends "quantum optics of quantum gases" to the field of ultracold molecules. Merging the quantum optical and ultracold gas problems will advance the experimental efforts towards the study of the light-matter interaction at its ultimate quantum level, where the quantizations of both light and matter are equally important.